2004
DOI: 10.1002/mabi.200400063
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Biomineralization Behavior of N‐Methylene Phosphochitosan Scaffolds

Abstract: Biomimetic growth of calcium phosphate over natural polymer may be an effective approach to constituting an organic/inorganic composite scaffold for bone tissue engineering. In this work, N-methylene phosphochitosan (NMPCS) was prepared via formaldehyde addition and condensation with phosphoric acid in a step that allowed homogeneous modification without obvious deterioration in chitosan (CS) properties. The NMPCS obtained was characterized by using FT-IR and elemental analysis. The macroporous scaffolds were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 14 publications
0
28
0
Order By: Relevance
“…The preparation of a range of bone-like materials has been reported [6,29,[42][43][44][45][46][47][48][49]. Natural bone is a biocomposite in which inorganic apatite crystals are deposited on collagen fibers woven into a three dimensional structure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The preparation of a range of bone-like materials has been reported [6,29,[42][43][44][45][46][47][48][49]. Natural bone is a biocomposite in which inorganic apatite crystals are deposited on collagen fibers woven into a three dimensional structure.…”
Section: Discussionmentioning
confidence: 99%
“…HAP-binding proteins have definitive HAP-binding sites based on acid side chains on amino acids. Proteins containing aspartic acid-rich sequences interact with crystals of calcium salt in a specific manner [50,51], and poly-glutamic acid sequences or poly-aspartic acid sequences are present in HAP-binding proteins [49]. From a comparison of Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is in this context that natural-based polymers have been put forward in the last few years. Within this group, the polysaccharides, like starch, [20][21][22] and chitosan, [23][24][25][26][27][28][29] have been highlighted as the most promising, as they may act as analogs of polysaccharides present in vivo and adopt their roles. 27 An example of such affinity is the structural similarity observed between chitosan and glycosaminoglycans.…”
Section: Introductionmentioning
confidence: 99%
“…27 An example of such affinity is the structural similarity observed between chitosan and glycosaminoglycans. 28 Several reports about chitosan, [23][24][25][26][27][28][29] the alkaline deacetylated product of chitin, have shown that this polymer might have a range of interesting properties, from biodegradability to biocompatibility, considered to be suitable for bone tissue engineering scaffolding. Nevertheless, chitosan still presents a challenge when compared to other materials, that is, the inability of being processed by means other than by solventbased technology, which frequently leads to the development of scaffolds with poor mechanical properties and insufficient control of its morphology.…”
Section: Introductionmentioning
confidence: 99%